Post-Pandemic Inflation Dynamics: a Comparative Study of the Fiscal Theory in the Czech Republic and France - Makovský, Petr; Descubes, Irena; Hřebík, František (ACTA VŠFS)
Background: In the post-2021 era, Central Europe grapples with enduringly high inflation rates, challenging the effectiveness of conventional monetary policy tools. Objective: This study aimed to shed light on these complex dynamics, offering insights into the effectiveness of fiscal strategies in an environment where conventional monetary policies appear increasingly inadequate. Methods: The Fiscal Theory of Inflation offers a straightforward model to examine the financial exchanges between governments and the public within a two-day economic setting. The framework explains the recurring patterns in government borrowing, taxation, and public expenditure, highlighting their impact on inflation and presents the focal point of this study. Results: Utilizing empirical survey data primarily from the Czech Republic and France, sourced from the Czech Statistical Office, the Czech National Bank, Banque de France, and INSEE, this study engages with the Fiscal Theory of Prices to elucidate these phenomena. Central to this analysis is the Fiscal Theory of Inflation, which argues that unanticipated inflation results in the devaluation of nominal treasury bonds, prompting a corresponding adjustment either in expected primary surpluses or the discount factor. This adjustment is crucial to ensure alignment between the total government debt's actual value and these surpluses' present value. Recommendation: The study aims to provide insights into these intricate dynamics, offering implications for the efficacy of fiscal strategies in an environment where conventional monetary policies increasingly prove inadequate. Practical relevance: This paper explores the implications of these persistent inflationary trends, focusing on the imperative of government debt recovery, as recognized by the newly elected government in the autumn of 2021. This research is helpful for any economist who opposes inflation measurement, targeting, or, most importantly, the belief that money grows on trees, allowing the government to fund public expenditures that many view as crucial. Originality/value: The paper is original, based on the ideas of J.H. Cohrane. The paper is an empirical test of the so-called fiscal theory on the example of France and the Czech Republic.